Tournaments with ex post heterogeneous agents - TSOULOUHAS, Theofanis (Institutional Knowledge at Singapore Management University, 2007)
This paper compares relative performance evaluation via tournaments to absolute performance evaluation via piece rates when agents are heterogeneous ex post, to make the point that agent heterogeneity compromises the insurance function of tournaments. In particular, we show that the more heterogeneous agents are the less insurance can be offered through tournaments and the less dominant tournaments are over piece rates. Thus, absolute performance piece rates should be preferred when agents are highly heterogeneous. However, even with heterogeneous agents, tournaments become more desirable when the number of agents or the uncertainty about the common shock increases sufficiently.